Conservation tillage systems: a review of its consequences for greenhouse gas emissions. (4th February 2013) - Abdalla, M.; Osborne, B.; Lanigan, G.; Forristal, D.; Williams, M.; Smith, P.; Jones, M. B.
Abstract Conservation tillage (CT) is an umbrella term encompassing many types of tillage and residue management systems that aim to achieve sustainable and profitable agriculture. Through a global review of CT research, the objective of this paper was to investigate the impacts of CT on greenhouse gas (GHG) emissions. Based on the analysis presented, CT should be developed within the context of specific climates and soils. A number of potential disadvantages in adopting CT practices were identified, relating mainly to enhanced nitrous oxide emissions, together with a number of advantages that would justify its wider adoption. Almost all studies examined showed that the adoption of CT practices reduced carbon dioxide emissions, while also contributing to increases in soil organic carbon and improvements in soil structure.